Family therapy for substance addicted adolescent and a case report - Kılıçarslan, Fatih (Journal of Dependence, 2007)
Family therapy is being applied on inhalant substance usingadolescent receiving treatment atÇEMATEM department of Bakırköy Mental Health Hospital – Istanbul since 2003 in this study, we present a case of family therapy applied to adolescents receiving treatment in a family environment.Y.U. is a 16 years old male adolescent using inhalant substance for 4-5 years. He doesn’t go to school, is jobless and on occasional runaway. He had received pharmacotherapy and individual therapy result in a bad solution. In addition to theses, we have applied systemic family therapy for 18 seance between March 2003 and June 2003. He received therapy once a week. Even though the full family participation was not received, either the mother or the father participated in all seances. The family has 5 members. The mother being a house wife, the father is a furniture manufacturer. He had days with no work and was taking alcohol frequently. Y.U. had a 3 years old brother. The sister, never participated the therapy seances, is married living in a different district. The parents, especially the mother, were determined the participated the seances.Y.U., in the early seances, could not control his anger. He was shouting and threatening. He would leave therapy room yelling and threatening. However, he state in the room until the end of the therapy in the later seances and could express his feelings in proper manners. He would be sitting closer to the family members; symbolically showing acceptance of his family.Even though 6 months had passed over the therapy, Y.U. is living with his family and is not using substance. He can control his feelings and has a job.Family therapy is not a usual treatment method applied to inhalant substance using adolescent. The case reported here gives the hope that family therapy can be helpful even in such cases. The systemic family therapy can have success in cases where the inhalant substance using adolescent has serious problems in family relationships.
Keywords: family therapies; volatile matter; dependence